Formação continuada na perspectiva das relações étnico-raciais: vivências de profissionais da educação infantil - Paiva, Amanda Barbosa de
The training and practice of teachers in addressing ethnic-racial diversity and ethnic-racial relations, especially in Early Childhood Education, have been a focus of interest among educational researchers. The Memória e Identidade –Promoção da Igualdade na Diversidade (MIPID) Program is part of the continuing education public policy for education professionals in the municipal school network of Campinas, promoted by the Municipal Department of Education (SME) or in partnership with other entities and institutions. This study aimed to investigate how Early Childhood Education teachers and professionals participating in the MIPID Program perceive their professional practice in addressing racial diversity and ethnic-racial relations after completing this continuing education program. Specifically, it sought to identify the challenges and potentialities of working with this theme in Early Childhood Education, analyze the difficulties and contributions of this training proposal, and explore significant experiences related to educational practices. The research was based on the Historical-Cultural Theory, emphasizing the concept of lived experience proposed by Vygotsky. Interviews were conducted with six professionals from the municipal education network of Campinas, all permanent public servants and participants in the program. The results indicate that participants consider the training a key enabler, particularly in deepening their understanding of Black and Indigenous themes and applying the acquired knowledge to their pedagogical practice. However, they highlight concerns regarding the approach to Romani culture, access to theoretical materials, and the training quality of the instructors. Among the challenges, they emphasize the need for long-term training focused on a single theme, the limited opportunities for sharing practices, and the lack of preparation for using specific materials in schools. Regarding the implementation of the theme in Early Childhood Education, participants emphasized the potential to integrate course content into pedagogical projects, as well as the importance of fostering collectivity and racial and cultural representation in schools. Nevertheless, they point out difficulties such as the solitary nature of teachers' efforts and the lack of engagement from the entire school staff. The experiences shared highlight processes of deconstructing stereotypes and prejudices, confronting racism and religious racism, strengthening identity and belonging, and recognizing human diversity. The study reinforces the importance of training programs like MIPID for effectively implementing ethnic-racial themes in Early Childhood Education, emphasizing the need for public policies committed to antiracist education.